Micro-finance selection criteria for customers in South Africa - Fritz, Christoffel C (My University, 2011)
Micro-finance serves a critical role in South Africa but it is yet to enjoy the attention of true marketing and customer focus (Rademaker, 2005). It is also an industry that finds itself under increasing political, regulatory and competitive pressures (Porteous & Hazelhurst, 2004). The opportunity to enjoy a position of competitive advantage and long term sustainability therefore exists for progressive micro-finance providers that focus on better understanding and addressing the needs and preferences of their customers. The purpose of the research was to identify and determine the relative importances of the borrowing decision criteria of customers in the micro-finance sector in order to aid market segmentation and product design efforts. The research included a pilot study of 12 micro-finance customers to facilitate the design of the research instruments. Subsequently, the responses collected from a non-probabilistic purposive sample of 88 micro-finance customers were analysed. The analysis was quantitative in nature and applied the conjoint analysis method to determine that on average, micro-finance customers regarded the loan amount of primary importance. Following in order of importance was the affordability of loan repayments, the duration of the repayment term, the service quality, the turnaround time taken to conclude the loan transaction, and finally the price (or total cost) of the credit. To investigate the existence of potential micro-finance segments with different needs and preferences, the output data of the conjoint analysis was further analysed using the principal components analysis and k-means clustering methods. The resulting five segments were profiled and labelled as “1 .Affordability and repayment term conscious big loan amount borrowers”, “2. Affordability constrained small loan amount borrowers”, “3. Service and price sensitive medium loan amount borrowers”, “4. Impatient affordability constrained big loan amount borrowers”, and “5. Affordability conscious service and price shoppers”.
MBA - WBS
Keywords: Micro-financing; Small traders; Small businesses; Micro-finance